Financial market complexity - Johnson, Neil F., 1961-; Jefferies, Paul.; Hui, Pak Ming. (Oxford ; New York : Oxford University Press, 2003)
This is a book about financial markets and draws on recent ideas from the highly topical science of complexity and complex systems, to address the following questions. How do financial markets behave? Why do financial markets behave in the way that they do? What can we do to minimize risk, given this behaviour?
Includes bibliographical references ([p. 252]) and index.
rua 20/02/15
Loans
Keywords: Finance -- Statistical methods; Finance -- Mathematical models; Statistical physics